Preceptor characteristics and the socialization outcomes of new graduate nurses during a preceptorship programme - Lalonde, Michelle (Nurs Open, 2016)
AIM: The purpose of this study was to explore the relationships between preceptor characteristics (emotional intelligence, personality and cognitive intelligence) and new graduate nurse socialization outcomes regarding turnover intent, job satisfaction, role conflict and ambiguity during a preceptorship programme. To date, no studies have explored these relationships. DESIGN: A cross‐sectional and multi‐site design with purposeful sampling. METHODS: Dyads of preceptors and new nurses were recruited at the end of their preceptorship programme. Pearson's correlational analysis was used to examine the relationships. RESULTS: A sample of 41 preceptors and 44 new graduate nurses participated in this study, making 38 dyads with complete data. The preceptor personality traits of openness, conscientiousness and emotional stability were significantly related to new graduate nurses who reported greater turnover intent, job dissatisfaction, role conflict and ambiguity. No significant relationships were noted between preceptor EI and IQ and the outcome of new graduate nurses.